Identified of Tobacco Industry Development in East Java: Error Correction Model Approach and The Tripled Layer Business Canvas Model Application - Mu'min, M Silahul; Anggara, Yoga Pury; Maulana, Reza Bagas (Journal of Developing Economies, 2018)
The agricultural sector is one of the main sectors in the Indonesian economy in addition to the industrial sector and the trade sector. In addition to the purpose of meeting the basic needs of the community, the agricultural sector also contributes to the Indonesian economic structure. In 2018, BPS (Central Statistics Agency) noted that the agricultural sector contributes 14% to GDP (Gross Domestic Product). East Java Province has enormous potential for the development of the agricultural sector today. Agriculture is still a leading sector for the economy of East Java in the digital era as it is today. Tobacco is one of the agricultural derivatives commodities that have an important contribution in the economy. Based on data from the Central Statistics Agency (BPS) from 2010-2016, there are four regions with large tobacco production in East Java, namely Jember, Probolinggo, Situbondo and Bojonegoro, which account for 2.01% of Java's Gross Regional Domestic Product (GRDP) East in 2016 with a gross added value of Rp. 27,321 billion. Business competition in the current digital economy era requires industry to be able to try to increase production capacity in the face of competition with similar industries. The purpose of this study is to analyze the factors that influence the development of the tobacco industry both in the short and long term and provide recommendations for sustainable and competitive tobacco industry development policies. This study uses the Panel Vector Error Correction Model (PVECM) method and the preparation of industrial development recommendations based on the Triple Layered Business Model Canvas (TLBMC). The results showed that the level of GRDP and land productivity were the main factors influencing the development of the tobaccoindustries and canvas in TLBMC capable of being the basis for supporting the development of the tobacco industry that is more holistic in the orientation of sustainable innovation business by considering three perspectives namely economic, environmental, and social impacts.   Key words : Panel Vector Error Correction Model, Tobacco of industriy, Triple Layer Business Model Canvas